Bulletin - New Straits Times, (2008)
Universiti Putra Malaysia's Medicine and Health Sciences Faculty is organising a seminar on Translational Research In Oncology. The Malaysia-Singapore initiative at the faculty's main lecture hall on jan 17 at 8.30am.